Concerns on the Results Reported in a Recently Published Meta-Analysis...Debray A, Ravanelli N, Chenette-Stewart O, et al. Effect of exercise training on blood pressure in healthy postmenopausal females: a systematic review with meta-analysis. Med Sci Sports Exerc. 2023;55(7):1317-1325. - Zhang, Jiaqi; Yu, Angus P. H.; Poon, Eric T. C.; Wong, Stephen H. S. (Medicine & Science in Sports & Exercise, 2025)
The article addresses concerns regarding a systematic review with meta-analysis conducted by Debray et al., highlighting potential statistical errors that could affect the interpretation of the findings. The authors critique the misuse of standardized mean differences (SMD) in reporting blood pressure effects, arguing that mean differences would be more appropriate given the uniformity of outcome measurements across studies. Additionally, they point out a unit-of-analysis issue related to the duplication of control groups in studies with multiple treatment arms, which could inflate meta-analytic weights. The authors emphasize the importance of methodological rigor in meta-analyses to ensure robust and clinically meaningful results.